Determining Promising Practices for Canadian School Food Programs: A Scoping Review. Issue 6 (2nd November 2022) - Everitt, Tracy; Engler-Stringer, Rachel; Martin, Wanda
ABSTRACT: In Canada, childhood obesity is increasing while 16% of children are food insecure. Schools provide an opportunity to promote healthy eating, yet, there is no national school food program. The purpose of this scoping review is to determine promising practices for Canadian school food programs. Using peer reviewed and gray literature in English and French published after 1970, we examined 35 publications for evidence of nutritional intake, nutrition education, improved educational attainment, promotion of health equity, and cultural awareness. Interest in school food programs is growing. Programs should address social determinants of health, food systems, and environmental and economic sustainability.